Sistem Pendukung Keputusan Pemilihan Sekolah Terbaik Di Kota Medan Dengan Menggunakan Metode AHP Berbasis Web - Resky Kestar (Cattleya Darmaya Fortuna, 2021)
In the selection of the best school for prospective students / students or who will continue their education. Many criteria that must be seen from the number of schools in the city of Medan, which is one of the factors determining the quality of the school. Because it only uses the help of newspaper media and brochures, many prospective students are confused or hesitant in determining which school they want to enter. Many schools are often not in accordance with the information in the newspaper media and brochures, this can certainly harm prospective students / students who want to enter the school. Thus many prospective students / students or guardians of students / students feel doubtful in determining which school to choose. Based on previous research on the selection of the best schools in the journal. The support system of decision determination of the favorite school of the private junior high school level using the analitycal hierarchy process method. The existence of a decision support system that is able to provide problem solving to make it easier for prospective students / students in determining the best school so that there is no confusion or doubt in determining the best school. The Analitycal Hierarchy Process (AHP) method can test the consistency of assumptions against an alternative in the determination of the best schools, Applications that use the Analitycal Hierarchy Process (AHP) method based on WEB is one application that can help in determining the selection of the best school, Analytical Hierarchy Process (AHP) is a functional hierarchy with its name input in the form of human perception.